Oneida lives : long-lost voices of the Wisconsin Oneidas - Lewis, Herbert S.; McLester, L. Gordon, III (Iroquoians and their world., 2005)
In this intimate volume the long-lost voices of Wisconsin Oneida men and women speak of all aspects of life: growing up, work and economic struggles, family relations, belief and religious practice, boarding-school life, love, sex, sports, and politics. These voices are drawn from a collection of handwritten accounts recently rediscovered after more than fifty years, the result of a wpa Federal Writers' Project undertaking called the Oneida Ethnological Study (1940-42) in which a dozen Oneida men and women were hired to interview their families and friends and record their own experiences and observations.